ESRA19-0255 Evidence-based management of pain after non-cosmetic breast surgery: a prospect review update. (30th August 2019) - Jacobs, A; Lemoine, A; Bonnet, F; Van de Velde, M
Abstract : Background and aims: Breast surgery is commonly associated with inadequately treated acute and chronic postoperative pain. the aim of this systematic review was to evaluate the available literature on postoperative pain and develop recommendations for optimal pain management after non-cosmetic breast surgery (NCBS). Methods: A systematic review using Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) with PROcedure SPECific Postoperative Pain ManagemenT (PROSPECT) methodology, was undertaken. Randomised controlled trials (RCTs) published in the English language from May 2006 until November 2018 assessing postoperative pain using analgesic, anaesthetic, and surgical interventions were identified from MEDLINE, EMBASE and Cochrane Databases. Results: 700 RCTs were identified, 56 RCTs met the inclusion criteria and were included in this review. Quantitative analysis suggests that dexamethasone and gabapentin reduced postoperative pain (p<0.05). the use of paravertebral blocks (PVB) also reduced pain scores (p<0.001), analgesic consumption (p<0.05) and the incidence of postoperative nausea and vomiting (PONV) (p<0.005). Intraoperative opioid requirements were documented to be lower when pectoralis (PECs) nerve block was performed (p<0.001) also decreasing postoperative pain scores and opioid consumption (p<0.05). Conclusions: We recommend preoperative dexamethasone and gabapentin to be added to the standard of care for NCBS. In case of major breast surgery a regional anaesthetic technique such as PVB or PECs block may be considered perioperatively for additional pain relief. PVB can also be used as a continuous infusion for postoperative pain management.